Mutational improvement of peanut - Prasad, Maddipatla V. R.; Mamede, Francisco Berilo Façanha; Silva, Fanuel Pereira da (Pesquisa Agropecuaria Brasileira, 2014)
A study was initiated to improve the peanut variety Tatu (Arachis hypogaea L., ssp. fastigiata Waldron, var. fastigiata), through induction of mutations for increased pod number per plant and better pod filling, using a chemical mutagen sodium azide (NaN3). The treatment with sodium azide at a concentration of 3mM was found to be the most efficient as well as effective for induction of desirable mutants. Among the ten productive mutants selected with varying degrees of improvement over the parent for the characters mentioned above, three of them Dwarf, Sd-HP and V3 consistently maintained their superiority in yield at significant levels over a period of three seasons including conditions of low rainfall. The mutants Dwarf and Sd-HP demonstrated improvement in pod number per plant, seed number per pod, shelling percentage and harvest index in the M4 generation and superior yield levels. Use of these mutants in peanut breeding is discussed.